Hospital classes: analysis of the guarantee of the right to education against the need for applicability / Classes hospitalares: análise da garantia do direito à educação frente à necessidade de aplicabilidade - Kleytonn Giann Silva de Santana; Paulo Ricardo Silva Lima; Renata Souza de Lima (Universidade Estadual de Alagoas, 2019)
Education is a right that every Brazilian citizen should have, with the union, states and municipalities in line with other public agencies, to develop strategies and policies that enable everyone's access without any distinctions, as recommended in the current Magna Carta. However, the realization of this right in hospital dependencies in all regions of Brazil is not contemplated, competing for a distance between the individual and access to knowledge and continuing education. In Alagoas, despite the state constitution and resolution 01/2016 affirming that education should be contemplated in hospital units, there is no effectiveness of this right, and therefore, it is necessary for efficient policies to realize this right foreseen in the paper. In view of the above, the main objective of this study is to analyze the legal provisions that guarantee the right to education in the hospital environment, having as a parameter the study of laws, decrees and resolutions on the subject that are (or should be) applied in the city of MaceióAL. The methodology used for the feasibility of the research was the bibliographical and documentary review, being used studies of notorious scientific relevance addressed in books, documents and other accessible sources.